MSME Empowerment and Development Program to Increase Consumer Satisfaction - Mohamad Toha; Neng Julfa Habibah (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2023)
The primary aim of this study is to examine the efficacy of an MSME empowerment and development initiative in enhancing consumer satisfaction at the Warung Nasi Hj establishment. Artificial intelligence (AI) is a field of study and research that focuses on the development The approach employed in this service encompasses the utilisation of customer surveys, interviews conducted with store owners, as well as the analysis of both qualitative and quantitative data. Dedication has observed a noteworthy enhancement in consumer satisfaction as a result of the adoption of a complete empowerment programme, encompassing initiatives such as product quality improvement, employee training, and novel marketing methods. The findings of the survey indicate that consumers have observed favourable improvements in various aspects, including product quality, customer service, and overall experience at Warung Nasi Hj. Ai. In addition to this, stall proprietors also observed an increase in revenue and a greater portion of the market. The aforementioned findings demonstrate that the implementation of programmes aimed at empowering and developing micro, small, and medium enterprises (MSMEs) can effectively enhance the quality of MSME operations and yield sustainable profits through the augmentation of consumer happiness and business expansion. This study aims to investigate the relationship between consumer satisfaction, empowerment of micro, small, and medium enterprises (MSMEs), business development, and marketing strategy.